PROBLEM EFEKTIFITAS PENCEGAHAN COVID-19 DI INDONESIA DALAM PERSPEKTIF SOSIOLOGI HUKUM - M. Syamsul Rizal, Athoillah Islamy, Kusroh Lailiyah (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
The spread of the corona virus (Covid-19) has become a disaster and an international problem whose impact is experienced by all citizens of the world, including the citizens of Indonesia. Various efforts to prevent the spread of covid-19 have been carried out by the Indonesian government. One of them, is Pembatasan Sosial Berskala Besar (PSBB). Nevertheless, the implementation of the PSBB is not as easy as imagined. In practice, there is not a slight contestation between the objectives of the government and the personal interests of the individual community. Therefore, this study aims to describe the extent of the effectiveness of PSBB policies in Indonesia. This study is a qualitative study. The main data source used is various reports on the conditions of implementing PSBB in various regions of Indonesia, both in the mass media coverage and various scientific researches. Meanwhile, secondary data sources, namely various studies relevant to the subject matter of this study. This type of research approach is empirical normative research. Meanwhile, the theory used as a knife for analysis is the theory of legal effectiveness from Soerjono Soekanto. This study concludes that the implementation of the PSBB policy in several regions in Indonesia in its practical level has not been able to deliver effectively. This is because there are problems in four aspects of the PSBB implementation policy, namely the rule of law, law enforcement, public awareness, and facilities (facilities)